Analisis Perubahan Pengetahuan Siswa SMPN 1 Indrapuri Aceh Besar Tentang Tajhiz Mayit Sebelum dan Sesudah Penyuluhan Tahun 2025 - Kurnia, Reza (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study examines the level of students' knowledge before and after the implementation of a counseling program on Tajhiz Mayit. The research, conducted on January 08, 2025, aims to evaluate the effectiveness of the counseling on Tajhiz Mayit in improving students' knowledge at SMPN 1 Indrapuri, Aceh Besar. The method used is a pretest-posttest design, measuring participants' knowledge before and after the counseling. Prior to the counseling, the pretest results showed that 2 participants (10%) had good knowledge, 11 participants (55%) had sufficient knowledge, and 7 participants (35%) had poor knowledge. After the counseling, all participants (100%) demonstrated an improvement in knowledge to the good category, with no participants remaining in the sufficient or poor categories. These results indicate that the counseling on Tajhiz Mayit was highly effective in enhancing participants' knowledge. The dramatic change in knowledge distribution from pretest to posttest shows that the intervention successfully improved participants' understanding comprehensively. This study highlights the importance of counseling as an effective method for enhancing students' knowledge and understanding of important topics, specifically Tajhiz Mayit.